Kyai Haji Abbas Abdul Jamil's Preaching Model: The Combination between Tradition Aspects with Psychosufism - Amirudin; Jajat Darojat; Farid Wajd; Abdul Karim; Amin Hidayat; Mohammad Fathi Royyani (Jurnal Penelitian, 2023)
This article discusses the religious thought of Kiai Abbas Abdul Jamil related to manhaj in doing da'wah and social approach and solutions to problems in the community. Literature that discusses the figure of Kiai Abbas Abdul Jamil Buntet, more about the side of his struggle and heroism, this study aims to explain the other side of Kiai Abbas Abdul Jamil related to religious thought and its approach to society. In discussing the idea of Kiai Abbas Abdul Jamil, researchers use a qualitative approach, data obtained through interviews with families and students/alumni about daily life and how to educate students. The Data were analyzed with the literature related to it. The results of this study include that the approach to the community conducted by Kiai Abbas Abdul Jamil in carrying out his missionary mission is through the system of Shari'ah, namely by applying qawā’id fiqhiyyah and cultural approaches and habits of society. The conclusion is that the problems in society require resolution in the right direction; kiai Abdul Jamil intelligently uses analytical skills qawā’id fiqhiyyah and the socio-cultural approach as manhaj in his preaching.